2015
DOI: 10.1007/s11250-015-0855-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiology of subclinical mastitis in dairy ewes in two seasons in Semnan province, Iran

Abstract: Twenty-one dairy ewe flocks selected by stratified random sampling were subjected to study the prevalence and etiology of subclinical intramammary infections and to assess the influence of parity on the prevalence of intramammary infections. Also, spontaneous cure rates were determined over study period. A total of 1192 milk samples were collected at 2 weeks after lambing until tenth-week postpartum. All flocks had hand milking; those which were classified by bacterial culture and California Mastitis Test (CMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Already Bergonier et al (2003b) reported a CNS prevalence in subclinical mastitis ranging from 25 to 93%. Similar results (42.9%) were recently observed also in Portugal in milk samples from clinically affected sheep udders ( Queiroga, 2017 ), in Iran in subclinical ovine mastitis ( Narenji Sani, Mahdavi & Moezifar, 2015 ), in Greece in dairy goats ( Gelasakis et al, 2016 ) and in Italy in both species ( Dore et al, 2016 ). The identification of Staphylococcus xylosus in sheep and Staphylococcus caprae in goats is also in agreement with the literature ( Bergonier et al, 2003b ; Contreras et al, 2007 ; ErgĂŒn et al, 2009 ), while Staphylococcus equorum was isolated only by Hariharan et al (2004) in sheep and by Contreras et al (2003) in goats.…”
Section: Discussionsupporting
confidence: 88%
“…Already Bergonier et al (2003b) reported a CNS prevalence in subclinical mastitis ranging from 25 to 93%. Similar results (42.9%) were recently observed also in Portugal in milk samples from clinically affected sheep udders ( Queiroga, 2017 ), in Iran in subclinical ovine mastitis ( Narenji Sani, Mahdavi & Moezifar, 2015 ), in Greece in dairy goats ( Gelasakis et al, 2016 ) and in Italy in both species ( Dore et al, 2016 ). The identification of Staphylococcus xylosus in sheep and Staphylococcus caprae in goats is also in agreement with the literature ( Bergonier et al, 2003b ; Contreras et al, 2007 ; ErgĂŒn et al, 2009 ), while Staphylococcus equorum was isolated only by Hariharan et al (2004) in sheep and by Contreras et al (2003) in goats.…”
Section: Discussionsupporting
confidence: 88%
“…aureus [ 42 , 43 ], but similar to observations in dairy cattle in some countries such as Uganda [ 44 ], as well as in modern cattle dairy farms where contagious pathogens have been controlled [ 45 – 48 ]. Higher prevalence of CoNS has also been reported for ovine or caprine mastitis in China, Iran, Israel, Italy, the Netherlands, New Zealand, Spain, and Sweden [ 49 – 59 ]. Whereas all these studies, including ours, suggest a potential role for CoNS in causing SCM, there is as yet no concrete evidence for a cause and effect relationship between the two [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mastitis is a common disease entity of Red Sokoto goat (RSG), accompanied by physical, chemical, pathological, and bacteriological changes in milk and glandular tissues [1,2]. The disease is usually classified as subclinical, acute, subacute, chronic, and gangrenous based on etiopathological findings and observations [3]. Predisposing factors such as poor management and hygiene, teat injuries, and faulty milking machines are known to hasten the entry of the infectious agents and the course of the disease [4].…”
Section: Introductionmentioning
confidence: 99%